2010
DOI: 10.1111/j.1365-2427.2010.02420.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive intraspecific genetic diversity of a freshwater crayfish in a biodiversity hotspot

Abstract: 1. The freshwater crayfish Cherax dispar (Decapoda: Parastacidae) inhabits coastal regions and islands of South East Queensland, Australia. We hypothesised that populations of C. dispar on different islands would be more genetically divergent from each other than populations from different drainages within the same island or on the mainland. 2. Phylogenetic and phylogeographic analyses were conducted on two mitochondrial genes (cytochrome oxidase subunit I & 16S ribosomal DNA) and one nuclear gene (Internal Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 63 publications
2
45
0
Order By: Relevance
“…An even stronger pattern of lineage disjunction occurs between the Fitzroy and the almost equally extensive Burdekin Catchment directly to its north (Unmack, ). Another inferred barrier occurs south of the Mary River, based on genetic data from various species including several fish (Hughes et al ., ; Wong, Keogh & McGlashan, ; Thacker et al ., ) and macroinvertebrates (Murphy & Austin, ; Sharma & Hughes, ; Bentley, Schmidt & Hughes, ). These barriers appear to define the natural distributional limits of Els.…”
Section: Discussionmentioning
confidence: 99%
“…An even stronger pattern of lineage disjunction occurs between the Fitzroy and the almost equally extensive Burdekin Catchment directly to its north (Unmack, ). Another inferred barrier occurs south of the Mary River, based on genetic data from various species including several fish (Hughes et al ., ; Wong, Keogh & McGlashan, ; Thacker et al ., ) and macroinvertebrates (Murphy & Austin, ; Sharma & Hughes, ; Bentley, Schmidt & Hughes, ). These barriers appear to define the natural distributional limits of Els.…”
Section: Discussionmentioning
confidence: 99%
“…Dark areas are creeks, lakes or swamps. Dotted lines represent a priori island ‘sides’ (Page & Hughes, 2007a; Bentley et al. , 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The present study grew out of a multi‐stranded risk analysis undertaken by the Queensland State government to document the ecological assets of NSI that depend on ground water (see Marshall, McGregor & Negus, 2006b). Existing data from two freshwater crustaceans on the island (Page & Hughes, 2007a; Bentley, Schmidt & Hughes, 2010) has suggested that there could be different communities on the eastern and western sides, meaning they could be complements and thus with potentially important implications for risk assessments and conservation plans. Data from the same two species (and studies) also implied that Fraser Island may also be bisected by a currently unappreciated border between freshwater communities, but this one between north and south.…”
Section: Introductionmentioning
confidence: 99%
“…In freshwater crustaceans, cryptic variation has been repeatedly pointed out by the analysis of molecular polymorphisms at the mitochondrial gene encoding for the cytochrome c oxidase subunit I (COI) Witt et al 2006;Apte et al 2007;Bentley et al 2010;Dawkins et al 2010;FilipovĂĄ et al 2010;Chiesa et al 2011;Klobučar et al 2013). Since genetic variability plays a crucial role in shaping the evolutionary paths for populations and species (e.g.…”
Section: Introductionmentioning
confidence: 99%